What Influences Kathmandu Valley Users’ Attitudes Toward Plastic Money: Evidence from an Ordered Logistic Model - Shakya, Bikesh; Puri, Vaibhav; Devkota, Niranjan; Paudel, Udaya Raj; Dhanusk, Krishna (The Journal of Economic Concerns, 2023)
The use of plastic money has grown over time. Previously availed by a few, the use of plastic money amongst people with bank accounts has surged tremendously. In 2020, it was discovered that over 78 lakh individuals in Nepal utilized plastic money. This study aims to analyse determining factors that affect users’ attitude toward plastic money in Kathmandu valley. The Kathmandu valley was chosen as the study location because people from many workgroups and locations travel here in quest of varied opportunities, resulting in a diverse range of viewpoints. Both primary and secondary data were used for gathering relevant information. Questionnaire of structured type was developed to gather the response from 404 respondents and convenient sampling method was employed for the selection of respondents. The data collected was analysed using ordered logistic regression. Findings from the study indicated that 95.79% respondents have knowledge regarding plastic money and users carry a positive attitude towards use of plastic money. However, if banks would enhance their ATM services, then respondents are more likely to use plastic money. This study thus concludes that though awareness about plastic money is gender neutral, however, males prefer to use plastic money more than female. Hence, the convenience, security and incentives brought in by cards over scores cash usage.